How do new therapeutic strategies for PCOS management influence the health of the affected individuals? The narrative review - Aleksandra Wójcik; Jan Wojtas; Mikołaj Margas; Konrad Warchoł; Karol Stępniak (Kazimierz Wielki University, 2022)
Introduction and purpose: Management of polycystic ovary syndrome (PCOS) is difficult since the exact pathogenic mechanism has not been established yet. Due to that fact, the substances registered to treat PCOS are still lacking efficacy and are associated with a number of adverse effects. The aim of this study is to review new possible treatment approaches.   State of knowledge: Inositol administered alone or combined with oral contraceptive drugs improves patients' hormonal status and alleviates the weight increase in comparison to oral contraceptive drugs on their own. Berberine reduces insulin resistance, improves lipid metabolism, and reduces inflammatory reactions. Glucagon-like peptide-1 receptor agonists have a better weight loss effect and less severe adverse reactions than metformin. Thiazolidinediones combined with metformin improve ovulation rate, acne and increase SHGB levels. Thiazolidinediones have also less severe adverse reactions than metformin and can be useful in patients who are not able to tolerate metformin.   Summary: The review has shown that inositol, berberine, glucagon-like peptide-1 receptor agonists andthiazolidinediones have promising therapeutic effects in terms of PCOS treatment, however, more research is needed to establish safety and efficacy of those agents. Nonetheless, results of this study may be utilized in the education of health specialists in endocrinology departments.